Comprehensive Treatment of Lower Eyelid Plasty Based on Intraoral Fixation and Redistribution of Lower Eyelid Fat. Issue 2 (17th March 2023) - Ding, Kun; Wei, Ranran; Zhang, Shan; Dong, Yanhui; Chang, Huanchao; Liang, Xiaoqin
Abstract : Background: Eye bags especially give an impression of aging and mental exhaustion. At present, the surgical methods of bags mainly include conjunctival approach and lower eyelid skin approach. With the continuous upgrading of the concept of facial esthetics, the lower eyelid pouch surgery for middle-aged and elderly patients pays more attention to reducing surgical trauma, improving tear trough deformity along with the effacement of lid‑cheek junction. Objective: This paper discusses the clinical effect of the lower lid blepharoplasty involved orbital septum fat repositioning based on oral fixation via conjunctival approach combined with relaxation skin resection in the treatment of eye bags in elderly patient. Methods: Fifty elderly patients underwent blepharoplasty between January of 2021 and June of 2021 at our hospital. The lower eyelid orbital septum fat was released along with the prezygomatic space and the premaxillary space were stripped through the conjunctival approach. The released cellulite was redistributed in the prezygomatic space/premaxillary space and fixed in the oral vestibular with 5–0 Polysorb through the middle facial tunnel. Finally, the appropriate skin was finally removed. Results: After operation, 48 patients were satisfied with the operation results, with tight lower eyelid skin and natural lid‑cheek junction. One patient with conjunctival infection was cured after 7 days of antibiotic eye drops. One patient felt foreign body when chewing, and the symptoms disappeared naturally after 5 days without treatment. Conclusion: For middle-aged and elderly patients with bags, the surgical method in this study not only has good postoperative effect, but also has small damage to the lower eyelid orbicularis muscle. The appearance is natural and the lower eyelid skin is tight. The effacement of lid‑cheek junction and recreating a smooth transition of lower lid cheek interface, which can correct lacrimal groove deformity. The patients have high acceptance and satisfaction, which can be widely used in clinical practice.